PRG5 Knockout Precipitates Late-Onset Hypersusceptibility to Pilocarpine-Induced Juvenile Seizures by Exacerbating Hippocampal Zinc Signaling-Mediated Mitochondrial Damage - Wang, Dandan; Jin, Mei-fang; Li, Lili; Liu, Yueying; Sun, Yuxiao; Ni, Hong (Frontiers in Neuroscience, 2021)
Introduction Epileptogenesis is understood as the plastic process that produces a persistent reorganization of the brain’s neural network after a precipitating injury (recurrent neonatal seizures, for instance) with a latent period, finally leading to neuronal hyperexcitability. Plasticity-related genes (PRGs), also known as lipid phosphate phosphatase-related proteins (PLPPRs), are regulators of mitochondrial membrane integrity and energy metabolism. This study was undertaken to determine whether PRG5 gene knockout contributes to the delayed hypersensitivity induced by developmental seizures and the aberrant sprouting of hippocampal mossy fibers, and to determine whether it is achieved through the mitochondrial pathway. Here, we developed a “twist” seizure model by coupling pilocarpine-induced juvenile seizures with later exposure to penicillin to test the long-term effects of PRG5 knockout on seizure latency through comparison with wild-type (WT) mice. Hippocampal mossy fiber sprouting (MFS) was detected by Timm staining. In order to clarify the mechanism of the adverse reactions triggered by PRG5 knockout, hippocampal HT22 neuronal cultures were exposed to glutamate, with or without PRG5 interference. Mitochondrial function, oxidative stress indicators and zinc ion content were detected. Results PRG5 gene knockout significantly reduced the seizure latency, and aggravated the lowered seizure threshold induced by developmental seizures. Besides, knockout of the PRG5 gene reduced the MFS scores to a certain extent. Furthermore, PRG5 gene silencing significantly increases the zinc ion content in hippocampal neurons, impairs neuronal activity and mitochondrial function, and exacerbates glutamate-induced oxidative stress damage. Conclusion In summary, PRG5 KO is associated with significantly greater hypersusceptibility to juvenile seizures in PRG5(–/–) mice compared with WT mice. These effects may be related to the hippocampal zinc signaling. The effects do not appear to be related to changes in MFS because KO mice with juvenile seizures had the shortest seizure latencies but exhibited less MFS than WT mice with juvenile seizures.